Prognostic Factors for Long-term Aesthetic Outcome of Infantile Haemangioma Treated with Beta-blockers - Mireille M. Hermans; Suzanne G.M.A. Pasmans; Marlies de Graaf; Aviël Ragamin; Elodie J. Mendels; Johannes M.P.J. Breur; Hester R. Langeveld; Martine F. Raphael; Peter C.J. de Laat; Saskia N. de Wildt; André B. Rietman; Corstiaan C. Breugem; et al. (Medical Journals Sweden, 2023)
Parents of infants treated with beta-blockers for infantile haemangioma are often concerned about the long-term aesthetic outcome. This cross-sectional study assessed the influence on the long-term aesthetic outcome of characteristics of the infantile haemangioma, the beta-blocker treatment, and the infant. The study included 103 children aged 6-12 years, treated with beta-blockers (propranolol or atenolol) for infantile haemangioma during infancy (age at treatment initiation ≤1 year) for ≥6 months. Dermatologists and parents scored the Patient Observer Scar Assessment Scale, and the child scored a visual analogue scale. Dermatologists identified whether telangiectasia, fibrofatty tissue, and atrophic scar tissue were present. The long-term aesthetic outcome of infantile haemangioma was judged more negatively by dermatologists and parents in case of a superficial component, ulceration, older age at treatment initiation, higher cumulative dose, and/or shorter follow-up time. According to children, infantile haemangioma located on the head had better aesthetic outcome than infantile haemangioma located elsewhere. Close monitoring, particularly of infantile haemangioma with a superficial component, is essential for early initiation of treatment, and to prevent or treat ulceration. These outcome data can support parental counselling and guide treatment strategy.